A stable hairpin preceded by a short open reading frame promotes nonlinear ribosome migration on a synthetic mRNA leader. - Hemmings-Mieszczak, M (1999)
The regulation of cauliflower mosaic virus (CaMV) pregenomic 35S RNA translation occurs via nonlinear ribosome migration (ribosome shunt) and is mediated by an elongated hairpin structure in the leader. The replacement of the viral leader by a series of short, low-energy stems in either orientation supports efficient ribosomal shunting, showing that the stem per se, and not its sequence, is recognized by the translation machinery. The requirement for cis-acting sequences from the unstructured terminal regions of the viral leader was analyzed: the 5'-terminal polypyrimidine stretch and the short upstream open reading frame (uORF) A stimulate translation, whereas the 3'-flanking region seems not to be essential. Based on these results, an artificial leader was designed with a stable stem flanked by unstructured sequences derived from parts of the 5'- and 3'-proximal regions of the CaMV 35S RNA leader. This artificial leader is shunt-competent in translation assays in vivo and in vitro, indicating that a low-energy stem, broadly used as a device to successfully interfere with ribosome scanning, can efficiently support translation, if preceded by a short uORF. The synthetic 140-nt leader can functionally replace the CaMV 35S RNA 600-nt leader, thus implicating the universal role that nonlinear ribosome scanning could play in translation initiation in eukaryotes.